OC-019 Adamdec1: A Novel Molecule Linked to Crohn'S Disease, is Associated with an Increased Susceptibility to Citrobacter Rodentium Colitis in the knock out Mouse. (4th June 2013) - O'Shea, N R; Smith, A M; Chew, T; Dunne, J; Segal, A W
Abstract : Introduction: Innate immunity is attenuated in patients with Crohn's disease (CD), with impaired neutrophil recruitment, delayed clearance of E. coli, and defective secretion of pro-inflammatory cytokines from macrophages 1, 2 . This primary macrophage defect may result in failure to eradicate bacterial flora entering the tissues and lead to the chronic granulomatous inflammation characteristic of CD. To discover the molecules responsible, transcriptomic profiles were obtained from cultured human macrophages from CD patients and controls. ADAMDEC1 a Disintegrin and Metalloprotease was under-expressed in ~10% of CD patients. This protein is almost exclusively found in macrophages and dendritic cells in the small and large bowel lamina propria. Here we describe the response of Adamdec1 -/- mice to an enteric bacterial infection with Citrobacter rodentium . Methods: Adamdec1 -/- and wild type mice were administered ~108 or 109 C. rodentium by oral gavage and body weight monitored for three weeks. At intervals mice were sacrificed and samples of serum, stool, colon and spleen were collected. Serum cytokine levels were measured and bacteria counted, in stool and spleen. Bowel inflammation was assessed histologically. Neutrophil and immune cell recruitment to the colon were measured by MPO assay and qPCR respectively. Results: During infection, control mice experienced a mild self-limiting colitis, with minimal weight loss. Expression of Adamdec1 was up-regulated in the colon and this normalised with resolution. Adamdec1 -/- mice were more susceptible to C. rodentium infection: they demonstrated dramatic weight loss (p < 0.001), a more severe colitis and a reduced survival at the higher dose (67% vs 0%, p = 0.009). Serum levels of TNF, IL-1β and IL-6 were significantly lower in the knock-out mice (p < 0.05). Impaired survival was associated with positive cultures of the organisms from the spleen (p = 0.02). Conclusion: By analysing the transcriptome of macrophages from CD patients we have identified a novel molecule involved in mucosal immunity. Further work is underway to elucidate the precise role of ADAMDEC1 in the immune response. Individuals with grossly attenuated expression levels may be at an increased risk of developing CD as a consequence of an impaired ability to handle enteric bacterial pathogens. Disclosure of Interest: None Declared References: Segal & Loewi, Lancet 1976 Jul 31; 2(7979):219–21. Smith AM et al. JEM 2009; 206:1883.